Biased Enforcement Expansion?: Sociodemographic Differences in Police Drug Testing for Suspected Narcotics Use 1993–2015 - Estrada, Felipe (The British journal of criminology, 2022)
Since the 1990s, Sweden has witnessed a steady increase in the control measures focused on drug offences. These changes are results of political dynamics once pushed by centre-right parties but thereafter embraced by Social Democrats in government. The article examines the structure of police controls of drug offences and the extent to which these controls have focused on different sociodemographic groups during the period 1995-2015. The study shows that this intensified control of minor drug crimes has resulted in successively larger proportions of youths from deprived areas being forced to provide samples of body fluids. The criminalization of drug use constitutes an example of the significance of crime policy for both crime levels and the composition of the offender population.